Hybrid routing protocol for quantum network based on classical and quantum routing metrics - Shahad A. Hussein; Alharith A. Abdullah (Institute of Advanced Engineering and Science, 2023)
A quantum repeater is the heart of a quantum internet that enables end-to-end communication over long distances using the quantum entanglement feature. Although this characteristic gives quantum networks tremendous power in terms of speed and security, it puts quantum networks, especially the quantum internet, in front of challenges, like transforming a short-distance quantum link into a long-distance link, in addition to entanglement routing for finding the best path within a quantum network. So, this research aims to propose a hybrid quantum routing protocol (HQRP) based on routing metrics of the classical networks like hops count, as well as metrics of the quantum network represented by the possibility of entanglement between end nodes in the network. As a result, a mathematical model was built to determine the optimal path among many paths within the quantum network, and it was implemented on our quantum network simulator. Finally, we concluded that the proposed algorithm gives the optimal path based on the highest entanglement probability and lowest number of hop count.